FORMATION LAWS FOR STRUCTURAL MODIFICATIONS IN GOLD NANOCLUSTERS - J.V. Golovenko; J.J. Gafner; S.L. Gafner (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2012)
On the basis of the tight-binding potential modeling by molecular dynamics method, structurization processes in gold clusters from 1,6 to 5,0 nanometers in diameter were investigated. Influence of crystallization on formation of the internal structure in gold nanoclusters within the limits of the canonical ensemble is investigated. Range of stability various crystal isomers are analyzed.